A diagnostic RNA sequencing assay for direct identification and interpretation of pathogenic variants in the FBN1 gene - Irshaid, Manal; Al Mansoori, Ghadeera; Sulaiman, Mohamed; Mohamed, Asjed; Abdoh, Mohammed; Shalaby, Youssef M.; Al-Zohily, Bashar; Batool, Aalia; Aleissaee, Sara; Alzyoud, Lara; Ali, Bassam R.; Al Saffar, Muna; et al. (Frontiers in Molecular Biosciences, 2025)
IntroductionThe extensive size and multi-exon structure and the tissue-restricted expression of the associated gene FBN1 challenge the genetic diagnosis of Marfan Syndrome (MFS). Current genetic diagnostic methods adopted clinically to confirm or rule out the disease diagnosis rely on high throughput DNA sequencing approaches, including whole exome or genome sequencing. While these approaches are powerful, they are costly, time-consuming, and labor-intensive, and they generate vast data sets that require computational and bioinformatic infrastructure to interpret. This study introduces an alternative sensitive, comprehensive, rapid, and cost-effective assay for genetic screening for MFS using whole blood RNA.MethodsWhole blood samples were collected in EDTA tubes, followed by immediate RNA and DNA extraction. A targeted RNA sequencing assay was designed to amplify and sequence the full coding region of FBN1 from whole blood, where Large overlapping cDNA fragments amplified from FBN1- RNA and directly sequenced, effectively addressing the challenge of low transcript expression utilizing nested PCR technique. The assay Applied to five unrelated families with suspected MFS enabled reliable detection of pathogenic variants identified by exome sequencing, and functional characterization of their transcriptional effects.ResultsThe assay identified four pathogenic FBN1 variants including one nonsense, two frameshift, and one missense, establishing the diagnosis in four cases. This corresponds to a diagnostic yield of 80%, exceeding that of whole exome sequencing, which identified variants in only three of the five families (60%).ConclusionBeyond variant detection, the assay elucidates how these variants influence RNA transcription and contribute to pathogenic mechanisms. An insight that is often overlooked by DNA sequencing approaches. This allowed us to identify distinct effects of each identified variant and recognize RNA slippage as a novel disease mechanism that has not been reported before in MFS. The developed assay introduces an improved approach to the clinical genetic testing of MFS, with potential applicability for diagnosing other conditions involving large, multi-exon genes.